Competing Articulation of National Belonging Vis-à-Vis Immigration: South Africa, Czechia and Slovakia Compared - Filipec, Ondřej; Kondo, Valerie; Macková, Lucie (PARTECIPAZIONE E CONFLITTO, 2024)
This paper examines contemporary forms of nationalism through the populist parties in South Africa, Czechia, and Slovakia. Despite South Africa’s progressive constitution, economic challenges, exacerbated by the COVID-19 pandemic and global crises, have fuelled anti-immigrant sentiments, the "Put South Africans First" and "Operation Dudula" are emerging as anti-immigrant movements, wanting to reclaim entitlements for South Africans. In Czechia and Slovakia, populist parties have resurfaced amid political narratives and economic concerns. The study employs critical discourse analysis, combining desk research and textual analysis, to contrast populist discourse on migrants in South Africa with that in Czechia and Slovakia, focusing on the recent tensions. The analysis extends to populist political parties such as the Freedom and Direct Democracy (SPD) party in Czechia, the People’s Party – Our Slovakia (ĽSNS), and Operation Dudula in South Africa, exploring their impact on public sentiment and government responses. By identifying commonalities and disparities, the paper contributes to understanding the complex interplay between nationalism, populism, and anti-immigrant sentiments in diverse national contexts.